1980
DOI: 10.1128/iai.27.2.391-396.1980
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic protection against bacterial infection in mice induced by vaccination of Propionibacterium acnes

Abstract: A single intraperitoneal injection of the phenol-treated cells of Propionibacterium acnes into mice showed nonspecific resistance against subsequent lethal doses of an intraperitoneal challenge of Klebsiella pneumoniae, Staphylococcus aureus, and Streptococcus pyogenes. The protection showed a biphasic pattern. The maximum protection, designated as the early phase protection, was seen in mice injected with P. acnes vaccine 1 to 2 days before the challenge, whereas the late phase protection was seen in mice vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Ear thickness was measured regularly for 78 days, revealing a biphasic ear-swelling pattern. This is consistent with previous findings illustrating a biphasic change in the activity of the mouse reticuloendothelial system after intraperitoneal injection with phenol-treated P. acnes (Kobayashi et al, 1980). The biphasic pattern was interpreted by the fluctuation in the number of macrophages and other host cells in the inflamed skins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ear thickness was measured regularly for 78 days, revealing a biphasic ear-swelling pattern. This is consistent with previous findings illustrating a biphasic change in the activity of the mouse reticuloendothelial system after intraperitoneal injection with phenol-treated P. acnes (Kobayashi et al, 1980). The biphasic pattern was interpreted by the fluctuation in the number of macrophages and other host cells in the inflamed skins.…”
Section: Discussionsupporting
confidence: 92%
“…These data implied that inactivated P. acnes vaccines may increase host immunity. Adversely, vaccination targeting whole bacterium may lack specificity (Kobayashi et al, 1980). Genomic (Bruggemann et al, 2004;Bruggemann, 2005) and/or proteomics approached may help in antigen selection for the development of component acne vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Although these killed P. acnes -based vaccines showed a good effect on acne patients, their effect is based on the non-specific modulation of the immune system of patients. Furthermore, It has been shown that mice immunized with killed P. acnes demonstrate non-specific resistance to challenge with other microbes [26] . A single intraperitoneal injection of phenol-treated P. acnes into mice showed non-specific resistance against subsequent lethal doses of an intraperitoneal challenge of Klebsiella pneumoniae, S. aureus, and Streptococcus pyogenes ( S. pypgenes ) [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, It has been shown that mice immunized with killed P. acnes demonstrate non-specific resistance to challenge with other microbes [26] . A single intraperitoneal injection of phenol-treated P. acnes into mice showed non-specific resistance against subsequent lethal doses of an intraperitoneal challenge of Klebsiella pneumoniae, S. aureus, and Streptococcus pyogenes ( S. pypgenes ) [26] . Recently, it has been shown that animals sensitized with P. acnes exhibit an increased susceptibility to E. coli lipopolysacharride (LPS) induced sepsis and [27] and liver failure [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been observed that i.p. inoculation elicits two distinct activities: (i) a short-term and local stimulation in the peritoneal cavity and (ii) a long-term and systemic stimulation of the reticuloendothelium (31). The results of our study indicate that, depending on the route of inoculation, either activated macrophages (after i.n.…”
Section: Resultsmentioning
confidence: 59%